Bio-butanol production from glycerol with Clostridium pasteurianum CH4: the effects of butyrate addition and in situ butanol removal via membrane distillation. Issue 1 (December 2015) - Lin, De-Shun; Yen, Hong-Wei; Kao, Wei-Chen; Cheng, Chieh-Lun; Chen, Wen-Ming; Huang, Chieh-Chen; Chang, Jo-Shu
Abstract Background Clostridium pasteurianum CH4 was used to produce butanol from glycerol. The performance of butanol fermentation was improved by adding butyrate as the precursor to trigger the metabolic pathway toward butanol production, and by combining this with in situ butanol removal via vacuum membrane distillation (VMD) to avoid the product inhibition arising from a high butanol concentration. Results Adding 6 g L−1 butyrate as precursor led to an increase in the butanol yield from 0.24 to 0.34 mol butanol (mol glycerol)−1 . Combining VMD and butyrate addition strategies could further enhance the maximum effective butanol concentration to 29.8 g L−1, while the yield was also improved to 0.39 mol butanol (mol glycerol)−1 . The butanol concentration in the permeate of VMD was nearly five times higher than that in the feeding solution. Conclusions The proposed butyrate addition and VMD in situ butanol removal strategies are very effective in enhancing both butanol titer and butanol yield. This would significantly enhance the economic feasibility of fermentative production of butanol. The VMD-based technology not only alleviates the inhibitory effect of butanol, but also markedly increases butanol concentration in the permeate after condensation, thereby making downstream processing easier and more cost-effective.